Students’ response to feedback : an exploratory study - Song, Geraldine (2020)
Much research work on teacher feedback has concentrated on the perceptions of students and teachers on feedback, but few studies have addressed the extent to which students respond to their teachers’ written feedback, particularly at the tertiary level. This study analysed the extent to which students made appropriate revisions based on the feedback they received. Forty-one sets of drafts and final papers written by first-year undergraduates were compared. The analysis focused on the main components of the grading criteria for the assignment: language and style, rhetorical structure, and format. The findings showed that the students paid more attention to feedback on the rhetorical structure of their writing. There was no statistically significant difference in the students’ revisions of language/style and format. The results suggest that the students were more concerned with macro issues concerning the clarity of their thesis/topic statements and the logical development of ideas, than with the mechanical aspects of writing. This study serves as a useful guide to teachers when providing feedback, and also serves to encourage further research involving different groups of students in different contexts.